2019
DOI: 10.1088/1757-899x/571/1/012055
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effect of Aflatoxin B1 on Heart, Lung, and Testis of Male Albino Rats: Histopathology Study

Abstract: The current study was carried out to investigate the toxic effects of aflatoxin B1 exposure on heart, lung, and testis of male Albino rats. Twelve healthy male Albino rats were used in the current study. They were divided equally into 2 groups (control and treated groups). The treated group was given aflatoxin B1 orally by a gastric tube at concentration 0.5 mg per kg of body weight for 7 day. The control group was given distilled water alone. At the end of experiment (1 week), the rats were killed under ether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The testes of the AF group demonstrated vacuolated STs with completely lost spermatogenic cells, widened interstitial space, germinal epithelium detachment from the basement membrane, and lower spermatogenic cell numbers. Kudayer et al [ 57 ] revealed that AFB1 administration to rats for seven days resulted in excessively vacuolated testicular cells with suppressed spermatogenesis. These results are in line with previous studies, which have established AF’s toxicity to the reproductive system [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The testes of the AF group demonstrated vacuolated STs with completely lost spermatogenic cells, widened interstitial space, germinal epithelium detachment from the basement membrane, and lower spermatogenic cell numbers. Kudayer et al [ 57 ] revealed that AFB1 administration to rats for seven days resulted in excessively vacuolated testicular cells with suppressed spermatogenesis. These results are in line with previous studies, which have established AF’s toxicity to the reproductive system [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the toxins, AB1 has long-term adverse effects on the liver, kidneys, brain, and especially the testes. This toxin can cause testicular inflammation resulting in impaired sperm production [27]. Various remedies have been proposed for the treatment of orchitis, but preference has been given to the use of biological constituents rather than chemical synthetic materials.…”
Section: Discussionmentioning
confidence: 99%
“…Among the toxins, AB1 has long-term adverse effects on the liver, kidneys, brain, and especially the testes. This toxin can cause testicular inflammation resulting in impaired sperm production [27]. Various remedies have been proposed for the treatment of orchitis, but preference has been given to the use of biological constituents rather than chemical synthetic materials.…”
Section: Discussionmentioning
confidence: 99%